The Role of Shopeepay Use in Improving Financial Inclusion by Using A Unified Theory of Acceptance an Use of Technology Model 2 (UTAUT 2) - Ainun Siti Fathonah; Irfan Nabhani; Hilmi Aulawi (Entrepreneurship Faculty, Universitas Garut, 2023)
This study aims to determine the role of the use of ShopeePay in increasing the Financial Inclusion of active ShopeePay users in Garut Regency, West Java, using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) approach. The research method used is a quantitative method, with a descriptive approach. The sampling technique used was purposive sampling. The hypothesis testing technique uses SEM-PLS with the SmartPLS 3.0 application, namely by conducting an Assessment of The Measurement Model which consists of a Convergent Validity test, a Discriminant Validity test, and a Reliability test, as well as an Assessment of the Structural Model) which consists of R-Square Analysis (R2), Q2 Analysis, Analysis of Direct Effects and Analysis of Indirect Effects. The results of testing the hypothesis show that: 1) Social Influence, Facilitating Conditions, Hedonic Motivation, and Price Value variables have a significant effect on Behavioral Intention to Use, 2) Facilitating Conditions, Hedonic Motivation, and Behavioral Intention to Use variables have an effect on Financial Inclusion, and 3) Influence, Facilitating Conditions, Hedonic Motivation, and Price Value have an indirect effect on Financial Inclusion through Behavioral Intention to Use as an intervening/mediation variable.